Dynamic Land Resources Management at the Mount Kelud, Indonesia - Wardhani, Puspita Indra; Sartohadi, Junun; Sunarto, Sunarto (Forum Geografi, 2017)
There is a contradictive situation between the theory that believes that high volcanic hazard areas should be for limited production zones and those areas that are intensively utilised for several production activities. This paper tries to discuss that contradictive situation from both the perspective of natural hazards and natural resources, therefore, the best options for the land utilisation pattern might be formulated at these high volcanic hazards areas. We conducted landscape analysis that covers volcanic morphology, volcanic materials, and both natural and artificial processes that modify the morphology and materials characteristics. The natural processes occurring in the high volcanic hazard might cover non-volcanic processes such as erosion and landslide. The artificial processes were usually considered as land utilisation activities by the local community. In such areas where both natural and artificial processes occurred, we conducted in-depth interviews to assess the community perception on thread and benefits of the last Kelud Eruption in February 2014. We evaluated the current land resources utilisation and portrayed the local adaptive land resource utilisation. There were three types of land resources available at the active volcano: space, natural scenery, and volcanic materials. The availability of these land resources was in a dynamic condition both in terms of quality and quantity. Immediately after the eruption, the natural scenery made the area attractive as a tourist destination. Following the high intensity of rainfall, the volcanic materials might be used as high-quality construction materials. The available space might be utilised for any purposes after the situation became relatively stable. The current space was mostly used for agricultural enterprises which accommodates the physical and socio-cultural characteristics of the active volcano environment.